Soluções irrigadoras no tratamento endodôntico: estudo het-cam e análise da incidência de dor pós-operatória - Demenech, Luciana Stadler (2019)
Sodium hypochlorite (NaOCl) solution is most commonly used for root canal system irrigation. Presents in the literature can select 0.5% to 8.25%. It has high antimicrobial power, but is related to its high toxicity that may be used postoperatively. Another frequently used irrigating solution is chlorhexidine (CLX), with a solution or gel form, with no potential for organic matter dissolution, but with great antimicrobial action. Due to the reduction of root canal system preparation time with single file systems and simplification of processes as a whole, the permanence of the irrigating solution in the root canal is small. Thus, a solution that controls the effective way to increase cleaning during chemical-surgical preparation is allowed as long as it maintains biological compatibility. In order to analyze the biocompatibility of different solutions, including 8.25% NaOCl, and an incidence of postoperative pain using these solutions, this article is composed of two articles. In the first one, the chicken embryo chorioallantoic membrane (CAM) was used by the HET-CAM method, the chicken egg test chorioallantoic membrane method and the Chicken Egg chorioallantoid membrane test. The tested solutions were physiological (control), CLX 2% and NaOCl (2.5%; 5.25% and 8.25%). Twenty-five membranes were analyzed, morphological changes and microcirculation available, with the aid of light microscope and photographs. The images were analyzed and quantified and the results obtained by analysis of variance (ANOVA) and Tukey test, Kruskal-Wallis and Mann-Whitney. The second article was evaluated with postoperative incidence, through randomized controlled clinical study, in patients treated with standardized endodontic treatment, single session and irrigation with a solution (NaOCl 2.5%; 5.25%; 8.25% or 2% CLX). The instrumentation was performed with a single file system, timed chemical-mechanical preparation time and the same shutter technique. The presence of pain was assessed as “yes” or “no” and intensity by Visual Analog Scale (VAS) at three different times after treatment (24, 48 and 72 hours). The data obtained were submitted to logistic regression. In the morphological evaluation, regarding hyperemia, NaOCl 8.25% presented significant difference compared to the other groups, except for NaOCl 5.25% (p = 0.096). In the coagulation analysis, CLX 2% was more annoying, with significant difference compared to 2.5% NaOCl (p = 0.038). Already NaOCl 8.25% had smaller number of vessels in the microcirculation. In the histological evaluation the most of inflammatory cells was observed with 8.25% NaOCl and tissue necrosis was present in all 5.25% NaOCl samples. Presence of fibroblasts were detected only in the control group. The results regarding postoperative pain, of the 180 patients evaluated, 169 answered the survey. Of these, 107 were women and the average age was 38.06 (SD = 14.371) years. Regarding the presence of postoperative pain (“yes” as a reference), after adjusting the variables, there was a significant difference in “time ≥ 10 minutes” (OR = 3.23; CI 95%: 1.05-9.91; p = 0.041), and “with obturation overflow” (OR = 13.6; CI 95%: 3.98- 46.9; p <0.001). For the outcome “24 hours postoperative pain”, the results also had a significant difference in relation to the same variables. NaOCl 5.25% represented 16.7% of the cases (OR = 7.10; CI 95%: 1.17-43.00; p = 0.003). After different methodologies it was possible to conclude that 8.25% NaOCl presented high toxicity in the CAM tests, however, compared to the other concentrations of the same solution and CLX, the effects were similar, such as tissue injury, acute instant inflammation and tissue necrosis. An extended preparation time and the leakage of obturator material are variables that influence the presence of pain. The 8.25% NaOCl solution can be used for root canal irrigation, as well as other concentrations, provided that the preparation time is reduced.